Sulforaphene suppresses growth of colon cancer‐derived tumors via induction of glutathione depletion and microtubule depolymerization. Issue 5 (24th March 2016) - Byun, Sanguine; Shin, Seung Ho; Park, Jiman; Lim, Semi; Lee, Eunjung; Lee, Chaeyoon; Sung, Dongeun; Farrand, Lee; Lee, Seoung Rak; Kim, Ki Hyun; Dong, Zigang; Lee, Sam W.; et al.
Abstract : Sulforaphene, an isothiocyanate abundant in radish, inhibits colon cancer cell growth with minimal toxicity toward normal cells. Sulforaphene induces oxidative stress through glutathione depletion and causes microtubule depolymerization exhibiting a potent anti‐cancer effect in vitro and in vivo. Abstract : Scope: Cruciferous vegetables harbor a number of isothiocyanates that have been recognized for their cancer‐related properties. Out of these, sulforaphene (a naturally occurring derivative of sulforaphane) has received little attention in studies of colon cancer and its mechanism of action remains to be elucidated. Methods and results: We observed that sulforaphene inhibited growth of human colon cancer cell lines HCT116, HT‐29, KM12, SNU‐1040, and DLD‐1, while exhibiting negligible toxicity toward nonmalignant cells. Sulforaphene induced G2/M phase cell cycle arrest and apoptosis of colon cancer cells analyzed by flow cytometry, concomitant with phosphorylation of CDK1 and CDC25B at inhibitory sites, and upregulation of the p38 and JNK pathways. It was further determined that sulforaphene is a potent inhibitor of microtubule polymerization while generating reactive oxygen species via the depletion of glutathione. These observations further extended into inhibitory effects against colon tumor growth in a mouse xenograft model. Conclusion: These findings demonstrate that sulforaphene may contribute to the anti‐tumor effects of cruciferous vegetables that contain sulforaphene and other isothiocyanates.